2017
DOI: 10.1038/s41598-017-03255-1
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Tracking Stress Echocardiography Uncovers Early Subclinical Cardiac Involvement in Pediatric Patients with Inflammatory Bowel Diseases

Abstract: Inflammatory bowel disease (IBD) is an established risk factor for cardiovascular disease (CVD). However, whether cardiac consequences present early in IBD is unknown. This is the first study in children aiming to unmask altered myocardial mechanics in IBD. We enrolled 50 consecutive normotensive children with Crohn’s disease (CD) (n = 28) or ulcerative colitis (UC) (n = 22). The study groups consisted of 18 patients with active inflammatory disease (mean age 14.6 ± 2.5 years) and 32 children with IBD in remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
11
0
2
Order By: Relevance
“…In previous studies, diastolic dysfunction was shown in both paediatric and adult inflammatory bowel disease patients. 11,29 Also, diastolic dysfunction was found to be correlated to coronary microvascular dysfunction in adult patients with no coronary risk factors in inflammatory bowel disease patients. 30 Early-onset inflammatory bowel disease defined as a monogenic inflammatory bowel disease group which is characterised with hyperinflammation and accompanied by autoinflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, diastolic dysfunction was shown in both paediatric and adult inflammatory bowel disease patients. 11,29 Also, diastolic dysfunction was found to be correlated to coronary microvascular dysfunction in adult patients with no coronary risk factors in inflammatory bowel disease patients. 30 Early-onset inflammatory bowel disease defined as a monogenic inflammatory bowel disease group which is characterised with hyperinflammation and accompanied by autoinflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…33 Left ventricular myocardial performance parameters were found to be depressed by speckle tracking echocardiography in inflammatory bowel disease. 11,29 In our study, we determined increase in septal and left ventricular end-systolic diameter in patients with early-onset inflammatory bowel disease. We can conclude that precaution in cardiac evaluation is necessary in early-onset inflammatory bowel disease subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Выполнение проб с физической нагрузкой с одновременной эхокардиографической оценкой систолической, диастолической функций ЛЖ и клапанного аппарата позволяет выявить взаимосвязь между симптомами, функциональной способностью пациента и гемодинамическими реакциями на нагрузку [8]. Появляются работы по исследованию возможностей применения технологии спекл-трекинг при стресс-эхокардиографии для оценки деформации миокарда ЛЖ [15][16][17].…”
Section: Introductionunclassified
“…STE is reproducible tool for the detection of myocardial strain and strain rate [ 11 , 12 ]. It has been successfully used to detect subclinical myocardial dysfunction in a variety of clinical settings such as arterial hypertension [ 13 ], systemic inflammatory disease [ 14 ], diabetes mellitus [ 15 ] and short-term alterations of glucose metabolism [ 16 ]. In 2013, the “ventricular theory” was fundamentally questioned by Goel et al as they reported a paradoxical decrease of LV strain in adults with neurally mediated syncope and a positive head-up tilt-table (HUTT) exam utilizing STE [ 17 ].…”
Section: Introductionmentioning
confidence: 99%